Islamic Education and Artificial Intelligence Integration Toward Ethical Governance and Responsible Learning Ecosystems Development - Ahmad Nabriz (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
The rapid advancement of Artificial Intelligence (AI) has transformed educational systems worldwide, creating both unprecedented opportunities and complex ethical challenges for higher education institutions. Within the context of Islamic education, AI integration requires careful consideration of ethical principles, governance mechanisms, and pedagogical objectives to ensure that technological innovation contributes to holistic human development rather than merely improving operational efficiency. This study aims to examine the integration of Artificial Intelligence within Islamic educational systems and explore its implications for ethical governance and responsible learning ecosystem development. Employing a qualitative library research approach concerning AI in education, Islamic educational philosophy, digital ethics, educational governance, and learning ecosystem transformation. The findings indicate that AI technologies can enhance personalized learning, educational accessibility, institutional effectiveness, and knowledge management. However, concerns related to algorithmic bias, data privacy, academic integrity, digital inequality, and ethical accountability remain significant challenges. The study proposes an integrative framework that combines AI innovation with Islamic ethical principles, including amānah (trustworthiness), ‘adl (justice), maṣlaḥah (public welfare), and ḥikmah (wisdom). The novelty of this research lies in developing a conceptual model that systematically connects Islamic educational philosophy, artificial intelligence governance, and responsible learning ecosystem development. The study concludes that sustainable AI integration in Islamic education requires a balance between technological innovation, ethical responsibility, and holistic learner development